2011
DOI: 10.1007/s10600-011-9776-9
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of panaxadiol

Abstract: One of the methods for studying the relationship between the chemical structure of compounds and their biological activity consists of the synthesis of compounds with a given structure and an investigation of their biological properties. In order to evaluate the influence of an additional 6D-OH group in panaxatriol on the biological activity of its semi-synthetic glycosides [1, 2], it became necessary to synthesize the corresponding panaxadiol monoglucosides. Panaxadiol (3E,12E-dihydroxy-20R,25-epoxydammarane)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The 1 H NMR data for the product were consistent with those of unlabeled 3 reported in the literature. 6 This suggested that 2 was selectively reduced by NaBH 4 at the 3-carbonyl position, as this position was more reactive than the 12-carbonyl position. 6 The radiochromatogram of the reaction mixture (30 h) also showed that 3 was the main radiolabeled product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1 H NMR data for the product were consistent with those of unlabeled 3 reported in the literature. 6 This suggested that 2 was selectively reduced by NaBH 4 at the 3-carbonyl position, as this position was more reactive than the 12-carbonyl position. 6 The radiochromatogram of the reaction mixture (30 h) also showed that 3 was the main radiolabeled product.…”
Section: Resultsmentioning
confidence: 99%
“…6 This suggested that 2 was selectively reduced by NaBH 4 at the 3-carbonyl position, as this position was more reactive than the 12-carbonyl position. 6 The radiochromatogram of the reaction mixture (30 h) also showed that 3 was the main radiolabeled product. The 3 and [3, H]PPD accounted for 75 and 5% of the total radioactivity, respectively, based to their peak areas.…”
Section: Resultsmentioning
confidence: 99%
“…A previous attempt by us to perform regio-and stereoselective glycosylation of the C-20 tertiary hydroxyl in 20S-protopanaxadiol 3,12-diacetate was unsuccessful [15,16]. Condensation of 20S-protopanaxadiol 3,20-diketone with D-acetobromoglucose with subsequent reduction of both C-3 and C-12 ketones also did not give the desired result [14]. We studied condensation of 12E,20S-dihydroxydammar-24-en-3-one (5) with 2 in order to prepare dammarane tetracyclic triterpenoids containing C-12 and C-20 galactopyranosides.…”
Section: = Galmentioning
confidence: 94%
“…The biological properties and mechanism of action of 20S-protopanaxadiol 3-O-E-D-glucopyranoside (ginsenoside Rh 2 ) [3-9] and 20S-protopanaxadiol 20-O-E-D-glucopyranoside, one of the principal metabolites of P. ginseng glycosides (compound K, M1) [1, 4,7,10,11], have been continuously studied for the last several years. We developed semi-synthetic preparative methods for preparing these compounds [12][13][14] that were based on chemical transformation of betulafolientriol, a dammarane triterpenoid and one of the constituents extracted from birch leaves (Betula pendula Roth., B. platyphylla Sukacz).Herein we continue research on the synthesis of glycosides of dammarane tetracyclic triterpenoids. We considered it advantageous to synthesize 20S-protopanaxadiol E-D-galactopyranosides that are close structural analogs of ginsenoside Rh 2 and metabolite M1 (compound K) in order to obtain new data on the structure-activity relationship of dammarane glycosides.…”
mentioning
confidence: 99%
“…These are glycosides of 20S-protopanaxadiol and those of 20S-protopanaxatriol, which differs from the former by having an additional hydroxyl on C-6. We prepared semisynthetic glycosides of 20S-protopanaxadiol and their analogs by chemical transformation of betulafolientriol, a component of the extract of birch (Betula) leaves [11][12][13][14]. Then, they were tested biologically [15][16][17][18][19][20].…”
mentioning
confidence: 99%